Transforaminal Endoscopic Lumbar Discectomy with versus without Platelet-Rich Plasma Injection for Lumbar Disc Herniation: A Prospective Cohort Study - Yi Jiang; Rujun Zuo; Shuai Yuan; Jian Li; Chang Liu; Jiexun Zhang; Ming Ma; Dasheng Li; Yong Hai (Pain Research and Management)
Objective. Transforaminal endoscopic lumbar discectomy (TELD) is an effective treatment for patients with lumbar disc herniation (LDH) with failure of conservative treatment. However, defects in the annulus fibrosus after TELD usually lead to a recurrence of LDH. Platelet-rich plasma (PRP) injection has shown promising potential for the repair of injured tissues. The combination of TELD and PRP injection has rarely been reported. Hence, this study aimed to evaluate the effectiveness, disc remodeling, and recurrence rate of LDH in TELD with or without PRP in LDH treatment. Methods. A total of 108 consecutive patients who underwent TELD were prospectively registered between July 2018 and December 2019 (https://clinicaltrials.gov/ct2/show/ChiCTR1800017228). Fifty-one and fifty-seven patients underwent TELD with PRP injections and TELD only, respectively. The visual analog scale (VAS) score for back and leg pain, Oswestry Disability Index (ODI), and MacNab criteria were evaluated, and perioperative complications were documented. The disc protrusion, spinal cross-sectional area (SCSA), and disc height were measured on MRI and evaluated preoperatively, postoperatively, and at regular follow-up. Results. All patients were followed up. Clinical improvement was noted in both groups. There were statistical differences in the VAS scores of back and leg pain and ODI between the two groups at 3 months, 6 months, and 1 year follow-up (P<0.05); the improvement in the PRP group was significant. The disc protrusion and SCSA on MRI in the PRP group showed better improvement, with lower recurrence rate, than that in the control group at the final follow-up (P<0.05). No adverse events were reported in our study following PRP injection. Conclusion. Our study showed that TELD with PRP injection was a safe and effective treatment for patients with LDH in the medium and long-term follow-up. PRP injection was beneficial for disc remodeling after endoscopic discectomy and decreased the recurrence of LDH.